A Study of Growth of Higher Education in Princely States: Examining the Growth of Higher Education in Princely Mysore: A Historical Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study intends to discover the priority given to Higher education in Princely Mysore. Theresearch study at this juncture on the said topic is relevant from the perspectives of policy making and issignificant to the philosophy of administering the higher education. Further the study will use to theeducationist, administrators, sociologists, historians and researchers. The scope of the study in futurealso calls for the comparative and critical analysis with regard to measures adopted by the Princely Stateon the said topic. The Modern era was started from 19th century in India and its states. Number ofeducated National leaders and Social reformers were known the significant role of higher education forNational development and Social reform. These National leaders and Social reformers were demanded toBritish government for start higher educational institutions. Therefore many higher educationalinstitutions were established along through India. Mysore State also a part of India thus many highereducational institutions were spread over in Mysore state. The study attempts to examine the growth ofhigher education and role of higher educational institutions to provide higher education in Mysore Stateduring Dewans period. Patronage of Dewans and maharajas on higher education in princely State ofMysore under the rule of British imperialism and what its impact on social system.